Masquerading in the midgut: a rare diagnosis in a patient with recurrent abdominal pain. Issue 5 (27th June 2019) - Smith, Philip J; Patel, Trusha; Reading, Nicholas; Giaslakiotis, Konstantinos; Hoque, Sami
Abstract : A 38-year-old woman who had been previously diagnosed with irritable bowel syndrome was seen in the outpatient clinic with a 2-year history of intermittent cramp-like abdominal pain which was often followed by watery diarrhoea. She had presented several times previously to the emergency department with episodes of severe pain and collapse although on arrival examination findings were mostly unremarkable other than some mild lower abdominal tenderness. On each occasion, the symptoms resolved spontaneously with conservative management. She had been extensively investigated by her general practitioner to establish the cause of her symptoms but all laboratory findings, cross-sectional imaging, ultrasound and oesophagogastroduodenoscopy to date were unremarkable. After being seen in gastroenterology outpatients' clinic, a colonoscopy was performed and was described as being macroscopically normal but microscopic evaluation of colonic biopsies suggested a possible 'resolving infection'. She was treated symptomatically, but within 6 months she represented to hospital with progressively worsening symptoms of severe abdominal pain, now associated with vomiting, followed by watery diarrhoea and then resolution of the symptoms. An abdominal CT scan was performed which showed a small intraluminal-filling defect in the mid-terminal ileum. A wireless capsule endoscopy was organised to further characterise the lesion although this was reported as showing no abnormality. Prior to any further outpatient investigations, she represented as an emergency to hospital in small bowel obstruction, underwent further cross-sectional imaging followed by surgical resection of the lesion. Histological characterisation revealed a small bowel inflammatory fibroid polyp.